Simultaneous dehydrogenation of 1, 4- butanediol to γ-butyrolactone and hydrogenation of benzaldehyde to benzyl alcohol mediated over competent CeO2–Al2O3 supported Cu as catalyst. (28th April 2020) - Bhanushali, Jayesh T.; Prasad, Divya; Patil, Komal N.; Reddy, K.Saidulu; Rama Rao, Kamaraju Seetha; Jadhav, Arvind H.; Nagaraja, Bhari Mallanna
Abstract: Hydrogen being a dynamically impending energy transporter is widely used in hydrogenation reactions for the synthesis of various value added chemicals. It can be obtained from dehydrogenation reactions and the acquired hydrogen molecule can directly be utilized in hydrogenation reactions. This correspondingly avoids external pumping of hydrogen making it an economical process. We have for the first time tried to carryout 1, 4-butanediol dehydrogenation and benzaldehyde hydrogenation simultaneously over ceria-alumina supported copper (Cu/CeO2 –Al2 O3 ) catalyst. In this concern, 10 wt% of Cu supported on CeO2 –Al2 O3 (3:1 ratio) was synthesized using wet impregnation method. The synthesized catalyst was then characterized by various analytical methods such as BET, powder XRD, FE-SEM, H2 -TPR, NH3 and CO2 -TPD, FT-IR and TGA. The catalytic activity towards simultaneous 1, 4-butanediol dehydrogenation and benzaldehyde hydrogenation along with their individual reactions was tested for temperature range of 240 °C–300 °C. The physicochemical properties enhanced the catalytic activity as clearly interpreted from the results obtained from the respective characterization data. The best results were obtained with 10 wt% of Cu supported on CeO2 –Al2 O3 (3:1 ratio) catalyst with benzaldehyde conversion of 34% and 84% selectivity of benzyl alcohol. The conversion of 1, 4-butanediol was seen to be 90% with around 95% selectivity of γ-butyrolactone. The catalyst also featured physicochemical properties namely increased surface area, higher dispersion and its highly basic nature, for the simultaneous reaction towards a positive direction. In terms of permanence, the Cu/CeO2 –Al2 O3 (10CCA) catalyst was quite steady and showed stable activity up to 24 h in time on stream profile. Graphical abstract: Image 1 Highlights: Ceria-Alumina supported copper catalyst was synthesized for simultaneous reactions. Effect of Cu/CeO2 and Cu/Al2 O3 on the catalytic activity for simultaneous reaction was determined. On simultaneous reaction 1, 4-butanediol and benzaldehyde conversion observed is 90% and 35%. γ-butyrolactone and benzyl alcohol selectivity observed was 95% and 84% at 240 °C. The catalyst exhibited stable activity up to 8 h.